2018
DOI: 10.1039/c7em00552k
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput evaluation of organic contaminant removal efficiency in a wastewater treatment plant using direct injection UHPLC-Orbitrap-MS/MS

Abstract: The removal efficiency (RE) of organic contaminants in wastewater treatment plants (WWTPs) is a major determinant of the environmental impact of these contaminants. However, RE data are available for only a few chemicals due to the time and cost required for conventional target analysis. In the present study, we applied non-target screening analysis to evaluate the RE of polar contaminants, by analyzing influent and effluent samples from a Swedish WWTP with direct injection UHPLC-Orbitrap-MS/MS. Matrix effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…the inuent : effluent peak area ratios were close to 1. 10 As shown in Fig. 1, the median outow : inow peak area ratios were 1.0 AE 0.10 for all the selected isotope-labeled standards except for glimepiride-d 5 (1.2), indicating that there was also no signicant difference in the matrix effects for a wide range of analytes between Södra Bergundasjön (inow) and Norra Bergundasjön (outow) lake water.…”
Section: Matrix Effectsmentioning
confidence: 79%
See 2 more Smart Citations
“…the inuent : effluent peak area ratios were close to 1. 10 As shown in Fig. 1, the median outow : inow peak area ratios were 1.0 AE 0.10 for all the selected isotope-labeled standards except for glimepiride-d 5 (1.2), indicating that there was also no signicant difference in the matrix effects for a wide range of analytes between Södra Bergundasjön (inow) and Norra Bergundasjön (outow) lake water.…”
Section: Matrix Effectsmentioning
confidence: 79%
“…All high-resolution MS data were processed using Compound Discoverer 3.0 following the workow from Li et al (2018), 10 consisting of peak picking, retention time alignment, unknown detection, isotope/adduct peak grouping, compound grouping, blank subtraction, and library searching using the online database mzCloud. Relevant parameters are provided in the ESI.…”
Section: Non-target Data Processing Workowmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the widespread use of these compounds their absence suggests efficient removal by the WWTP, which is supported by literature data. [49][50][51] Naproxen was detected in SW only which could be due to efficient bacterial degradation in the HZ. 52 Elevated concentrations of the TPs guanylurea, O-desmethylvenlafaxine and valsartan acid were also observed, in some cases exceeding their respective parent compound concentrations by over an order of magnitude.…”
Section: Pom Proles In the River Erpementioning
confidence: 99%
“…Iron-based sensors are used for this purpose. A study revealed that, in the presence of hydrogen peroxide, azo dyes (reactive yellow and reactive black) are degraded by ferrous oxalate reducing agent with surface-modified magnetite NPs . This degradation goes through Fenton’s reaction mechanism, in which hydrogen peroxide is reduced by a ferrous oxalate and produces hydroxyl (OH – ) free radicals through contaminated degradative organic contaminants via breaking of a covalent bond.…”
Section: Environmental Remediation By Hematite and Magnetitementioning
confidence: 99%